Signal Enhancement of Elements with Different Ionization Potential by Organic Solvent in ICP-MS - Guo, Wei; Jin, Lanlan; Hu, Shenghong (Asian Journal of Chemistry, 2014)
Signal enhancement of elements with different ionization potential by organic solvent in inductively coupled plasma mass spectrometry was investigated. In the presence of the 3 % methanol or 4 % glycerol, the enhancement factors were in the range of 1.5 to 2.8 compared with the aqueous solution for high ionization potential elements (e.g., As, Se etc.), while the factors were less than 1.5 for the low ionization potential elements (e.g., Ce, In etc.). Signal enhancement caused by sample nebulization-transport efficiency improved was less than 1.5, which was obtained by detecting the sample aerosol collected with cold trap. The degrees of ionization of As and Se in organic solvent were increased to 69-71 and 56-58 %, respectively. However, In and Ce were only slightly increased with organic solvent. Our results demonstrated that signal enhancement of elements with high ionization potential was mainly attributed to the increased degree of ionization in plasma, while the low ionization potential elements were mainly attributed to the improved sample nebulization-transport efficiency.